Formulation Of Mephenamic Acid Granules With Pvp And Avicel Mixture On The Physical Of Granules - Juvita Herdianty; Arif Wijayanto; Atary Anggita (Universitas STRADA Indonesia, 2023)
Mefenamic acid is a drug that is often used to relieve pain. Mefenamic acid is a drug used as an analgesic, antipyretic, and non-steroidal anti-inflammatory drug (NSAID). In the BCS (Biopharmaceutical Classification System) it is included in the class II category, namely its low solubility with high permeability. To overcome this, it is necessary to make efforts to increase solubility to obtain good bioavailability. This study aims to formulate granules using a mixture of Polyvinyl Pyrrolidone (PVP) and Avicel for the physical properties of the granules in three formulations. Preparation of granules using the wet garnulation method by making three formulations with varying concentrations of PVP, namely 1%, 2% and 3%. The results of the evaluation of the physical properties of mefenamic acid granules showed that the flow properties of the three formulas met the requirements, namely > 10 grams/second. The water content test showed that the three formulas met the requirements with a range of 2-5%, while the angle of repose test of the three formulas was only formula 1 which met the requirements, namely less than <30o.